An Unusual Presentation of Pediatric Conjunctival Mucosa-Associated Lymphoid Tissue Lymphoma - Samantha Bobba; Christopher Go; Amanda Charlton; James Smith; Maciek Kuzniarz; Subhashini Kadappu (Case Reports in Ophthalmological Medicine)
Ocular adnexal mucosa-associated lymphoid tissue (MALT) lymphoma is uncommon in the pediatric population. Initial misdiagnosis is common and there is lacking consensus regarding the optimal approach to treatment. Herein, we report an atypical presentation of pediatric conjunctival MALT lymphoma and review the presentation and management of this rare condition.